Narrating Memory: Weighing up the Testimony - Coetzee, Jan K. (Qualitative Sociology Review, 2021)
Memory is the ability to store, maintain and recall information and experiences. Although predominantly an individual attribute, memory coincides with the life-world, with consciousness and with the ability to define reality – all of which are shared with others. When analysing narratives the sociologist needs to situate individual memory within its broader context. The article follows the argument that individuals acquire their memories within a broader social context. They also recall and localise their memories within a broader social context. This article interprets a remarkable testimony: the story of a former political prisoner who circumcised a large number of young fellow inmates in the notorious prison on Robben Island, South Africa, during the period of Nelson Mandela‟s incarceration. The article relates the narrative in question to the life-world of the narrator and to his experiences whilst serving his 18-year prison sentence. It reflects on the epistemological questions regarding memories. Memory as recollection, as reconstruction of events and information, and as process of re-membering come under the spotlight. Narratives that are often repeated start taking on a life of their own – particularly in the case of trauma memories. When analysing these narratives, the sociologist needs to distinguish between objective markers and subjective interpretation. Memory does not constitute pure recall by the individual. The article illustrates the effect of intersubjective and collective factors on the process of remembering. It calls for a reflexive process to identify, re-interpret and unpack the process of remembering.